Missing Concept Image dan Mis-in Concept Image pada Materi Segi Empat Ditinjau dari Gaya Kognitif - Agustine Dwi Kurniawati Pamarna; Dadang Juandi; Al Jupri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The relationship between types of quadrilaterals is one of the concepts that students must master. However, based on literature studies, a lot of students made mistakes in determining the relationship between types of quadrilaterals. This research aims to describe missing concept images and mis-in concept images on quadrilateral concepts. When a concept's example is classified as not being an example of that concept, it is called a missing concept image; conversely, when a concept's non-example is classified as an example of that concept. A factor which can affects students' concept image is cognitive style. This research used a qualitative research design with a hermeneutic phenomenological approach. The subjects of this research were two students in 7th grade, each with field-dependent and field-independent cognitive styles. This research used two instruments, namely the GEFT test instrument to determine the type of student's cognitive style and a test instrument with two-tier multiple-choice questions to understand students' concept image of the relationship between types of quadrilaterals. The results of the research showed that missing concept images and mis-in concept images occurred in a student with field-dependent cognitive style, while in student with a field-independent cognitive style there was a mis-in concept image. The results of this research can be used as a consideration in designing learning that can minimizes concept image errors.